2016
DOI: 10.1016/j.ijscr.2016.10.042
|View full text |Cite
|
Sign up to set email alerts
|

Report of a case with gallbladder carcinoma: P53 expression of the peritumor epithelium might predict biliary tract recurrence

Abstract: HighlightsThe over-expression of P53 protein in gallbladder carcinoma is a biomarker correlating with a poor survival. However, the significance of P53 expression in peritumor tissues is unknown. We report a case of gallbladder carcinoma where the operative specimen showed over-expression of P53 on the peritumor epithelium, and early recurrence developed at the biliary tract.The immunohistochemical staining of the GB wall or surgical stump for a surgical specimen of GBC may be crucial to predict the bile duct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…In their case study, though the remnant of the cystic duct after surgery exhibited no signs of neoplasm when analysed with H&E staining, significant p53 overexpression was observed using immunostaining. The patient suffered a recurrence in the bile duct after 2.5 years [71].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In their case study, though the remnant of the cystic duct after surgery exhibited no signs of neoplasm when analysed with H&E staining, significant p53 overexpression was observed using immunostaining. The patient suffered a recurrence in the bile duct after 2.5 years [71].…”
Section: Discussionmentioning
confidence: 96%
“…Under normal circumstances, p53 inhibits proliferation of stressed and damaged cells thereby effectively stopping tumour development [69]. Mutations of the TP53 gene is one of the common genetic abnormalities found in most human cancers [70,71]. The most common mechanism of inactivation of p53 arises from point mutation that results in a translational product that has altered conformation and defective functionality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While some studies indicate that overexpression of p53 could be an early event in the carcinogenesis of well-differentiated adenocarcinomas of the gall-bladder [13], others define p53 overexpression as a late event in the carcinogenesis process due to increased levels observed in samples from significantly progressed GBC [14,15]. p53 levels has been suggested as a means to predict recurrence of malignancy after surgical resection by immunostaining of remnant tissue sample [16]. Kaur et al, linked p53 overexpression inversely to the grade of tumour and suggested p53 might not play a role in the metastasis of GBC [17].…”
Section: P53 • 1031mentioning
confidence: 99%
“…While some studies indicate that overexpression of p53 could be an early event in the carcinogenesis of well-differentiated adenocarcinomas of the gall-, others define p53 overexpression as a late event in the carcinogenesis process due to increased levels observed in cases from ominously progressed GBC [10]. P53 levels has been suggested as a means to predict recurrence of malignancy after surgical resection by immunostaining of tissue sample [11]. Kaur et al, linked p53 overexpression inversely to the grade of tumour and suggested p53 might not play a role in the metastasis of GBC [12].…”
Section: P53mentioning
confidence: 99%